Asimetría territorial tributaria en los entes subnacionales de México - Alejandro González García; Zeus Omar Trejo y Cruz; Yesenia del Carmen Trejo Cruz (Atlantic Review of Economics (ARoEc), 2020)
– Addressing the tax asymmetries of public entities in the Mexican territory, opens several possibilities of studies, which includes the magnitude and incidence of imbalances of the functions that empower the tax authorities in the country. Currently, this problem is observed in the face of the distribution of public resources, which proved inefficient to meet collective needs, given the shortage in some cases of supplies in the main scenarios of the economic rectory, which group the items such as education, health and job. The society receives the results and effects of a public policy aimed at meeting partial objectives, which to a large extent may not correspond to a fair social application of the budget; therefore, it is considered the legitimization of attributions of origin, which support the assignments, in the absence of sufficiency as constitutionally autonomous entities.
Keywords: K4; K49; 330; Federation; subnational entities; competencies; taxes; social development